Peran Agama dalam Membangun Toleransi dan Kerukunan Sosial di Tengah Keragaman Masyarakat: Studi Kasus di Kabupaten Pulau Morotai - Sahbi Diti; Rifaldi Ahmad; Mustamin Giling (Al-Kindi, 2026)
This study aims to analyze the role of religion in fostering tolerance and social harmony within the diverse community of Morotai Island Regency, North Maluku. Employing a descriptive qualitative approach, the research was conducted through in-depth interviews, participatory observation, and document analysis involving religious leaders, educators, and interfaith communities. The findings reveal that religion functions not only as a system of spiritual belief but also as a social instrument that strengthens solidarity and social cohesion in a plural society. Religious practices in Morotai reflect a living form of “social religion,” where religious values are integrated with local wisdom such as pela gandong, deliberation, and mutual cooperation. Furthermore, education, media, and the role of religious figures are identified as key factors in reinforcing the social ecology of tolerance. The study concludes that harmony in Morotai is not accidental but a social construct rooted in inclusive religious values and sustained communal practices.